Beyond Classroom Assessment as new norm approach / Nor Hafizah Hanis Abdullah and Roziah Keria - Abdullah, Nor Hafizah Hanis; Keria, Roziah (Unit Penerbitan FKAPP, 2020)
Traditional learning methods confined with textbook and classroom environment are no longer appropriate for the Education 5.0 approach. Indeed, generation Z students nowadays desperately need a different approach to pique their interest to deepen their knowledge especially in the field of engineering. In addition, with the current situation facing the challenge of the Covid- 19 pandemic, the needs for students’ access to the world outside the classroom is very much needed. With that, the instructors of Soil Mechanics course have taken the initiative to apply the concept of ‘Beyond Classroom Assessment’ to enhance the teaching and learning process, particularly to capture the student’s attention during this challenging Covid-19 period.